Apicultura entraves e perspectivas no Território do Velho Chico: ações de extensão - Santos, Felipe Nonato; Souza, José Augusto Santos; Alves, Emanuele Felipe; Souza, Ivna Herbênia da Silva; Borba, Tatiana Santos (Cadernos Macambira, 2021)
Ver texto em PDF